An Analysis of Reading Techniques and Perceptions for Student’s TOEFL Success in UPT Bahasa University of Riau - Gundary, Puspa; Gusparia, Gusparia (Journal of English Language and Education, 2025)
TOEFL is a widely recognized measure of English proficiency, yet many EFL students in Indonesia continue to face difficulties, especially in the reading section. Despite having been introduced to various reading strategies, there appears to be a disconnect between theoretical knowledge and practical application during test-taking. This study aims to investigate the efficacy of reading techniques in improving students’ TOEFL reading performance. Using a descriptive quantitative design, data were collected from 35 second-year law students at Riau University through TOEFL-style reading tests and questionnaires. Results showed that while students frequently used strategies such as rereading and identifying main ideas, more analytical techniques like summarizing and predicting were underutilized. The findings suggest that instruction should focus on reinforcing both basic and higher-order reading strategies to bridge the gap between knowledge and execution. Enhancing strategy use may significantly improve students’ TOEFL reading outcomes.